Decreasing in Acid Number of Patchouli Oil by Different Natural Adsorbent and Variation of Contact Time - Tri Esti Purbaningtias; Bayu Wiyantoko; Puji Kurniawati; Mustika Kusuma Sari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2014)
One way for improving (of improving atau to improve) the quality of patchouli oil was to reduce the acid number. Acid number could be reduced with the use of natural adsorbents. The decreasing percentage acid number of patchouli oils using adsorbents zeolites, bentonite, rub ash, and activated carbon, respectively 4.71 %; 1.45%; 7,84%; and 4.64%. The contact time could influence the decrease in acid number of patchouli oil. The longer the contact between adsorbent and oil could caused a decrease in acid number. Maximum contact time for rub ash was 15 hours with a maximum adsorption capacity of 14,34% for 0.1 gram adsorbent